Non-Dutch Petitions in the Seventeenth-Century Dutch Atlantic - van den Tol, Joris (Early Modern Low Countries, 2020)
This article argues for the centrality of petitions for colonial administration in the Dutch Atlantic. Moreover, through a study of non-Dutch petitioners, it demonstrates the diversity of individuals that exercised influence on colonial decision-making. This adds an important understanding of political exchanges to the well-established understanding of the Atlantic world as based on inter-imperial, cross-cultural, and multi-ethnic economic exchanges. The colonial inhabitants did not stand idly by as decisions in and from the European metropole or West India Company (WIC) administrators invaded their lives, but instead actively attempted to influence the rules and regulations that governed them. The space that allowed for this on-the-spot negotiation between the colonial government and those individuals it governed was open to virtually everybody and the topics covered were equally as varied, ranging from local decentralized authority to regulations for colonial commodities and issues of religion.